Engine size and proportion of catch kept affects fish catch in Pujada Bay, Davao Oriental - Arianne Kay Liguez (Davao Research Journal)
This study aimed to calculate the catch per unit effort (CPUE) and determine the status of the finfish population in Pujada Bay. This was conducted through semi-structured interviews, focus group discussion, and validation of actual catch sampling/logbook information taken from the interviews. Fishers mostly catch bigeye scad (Selar crumenopthalmus), flat needlefish (Ablennes hians), horseface unicornfish (Naso fageni), purple eyebrowed tuskfish (Choerodon zamboangae), silver pomfret (Pampus argenteus), and African red snapper (Lutjanus agennes) in Barangay Tamisan and skipjack tuna (Katsuwonus pelamis) and yellowfin tuna (Thunnus albacares) in Barangay Macambol. Results relating socioeconomic and fisheries variables to catch did not produce significant results. Further analysis using regression showed that normal catch was influenced by engine size and the proportion of catch kept by fishers (P≤0.05). Analysis of CPUE of fishers in Tamisan also revealed significant differences with the best catch having the highest CPUE (1.57 kg/hr), normal catch (0.62 kg/hr), and worst catch (0.27 kg/hr) with haul time of 5.46 hours. This was also similar in the case of Macambol which showed significant differences in the catches e.g. best catch having the highest CPUE (7.08 kg/hr), normal (4.37 kg/hr), and worst catch (2.54 kg/hr) with haul time 9.23 hours. Most species caught in Pujada Bay between Tamisan and Macambol are piscivores, other species are molluscivores, omnivores, carnivores, planktivores, and herbivores. Engine size in horsepower and proportion of catch kept by fishers affected the number of fish caught.